Studi Pengembangan Objek Wisata Danau (Studi Kasus: Danau Tendetung di Kabupaten Banggai Kepulauan) - Yustikasari Mappa; Rudi Latief; Emil Salim Rasyidi (Fakultas Teknik Universitas Bosowa, 2022)
This study aims to analyze knowing what factors influence the development of Lake Tendetung tourism objects and how the strategy for developing Lake Tendetung attractions in Banggai Islands Regency is.This study uses a qualitative approach and a quantitative approach with the data collection process through observation, documentation and questionnaire surveys where the sample is drawn using the purpose sampling method. The data obtained were then analyzed using multiple linear regression analysis and SWOT analysis.From the results of the multiple linear regression analysis that has been carried out, it can be concluded that the factors that have a significant effect on the development of the Tendetung Lake tourism object are the variables of tourist attractions, tourist facilities, tourism infrastructure, promotion and hospitality. Then from the results of the SWOT analysis using the SO strategy, which is to use strength to take advantage of opportunities as much as possible.